2010
DOI: 10.1002/elan.201000544
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Capacity by Using Xanthine Oxidase Bioreactor Coupled with Flow‐through H2O2 Amperometric Biosensor

Abstract: A new flow system for antioxidant capacity (AOC) estimation, consisting of a bioreactor, containing immobilized xanthine oxidase (XOD), coupled with a H 2 O 2 amperometric biosensor, based on Os-wired horseradish peroxidase, was developed. The H 2 O 2 , resulting from the enzymatic reaction between xanthine (XA) and XOD, was amperometrically monitored at À0.1 V vs. Ag/AgCl/KCl sat , in order to avoid the electrochemical interferences. Two protocols were used to perform the AOC evaluation: "steady-state", when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…The H 2 O 2 resulting from the enzymic xanthine was amperometrically monitored at -0.1 V vs. Ag/AgCl/KCl sat, and it was reported that this potential value applied avoided interferences. The antioxidant capacities of the analysed commercial beverages were consistent with those furnished by DPPH· and Folin-Ciocalteu assays [123].…”
Section: Amperometrysupporting
confidence: 78%
“…The H 2 O 2 resulting from the enzymic xanthine was amperometrically monitored at -0.1 V vs. Ag/AgCl/KCl sat, and it was reported that this potential value applied avoided interferences. The antioxidant capacities of the analysed commercial beverages were consistent with those furnished by DPPH· and Folin-Ciocalteu assays [123].…”
Section: Amperometrysupporting
confidence: 78%
“…2 However, in recent years, a great effort has been done in the use of more sophisticated and precise bioanalytical methods such as those based on electrochemical sensors and biosensors, in order to improve the detection performance. 8 In general, spectrophotometric techniques are simple, rapid and not expensive, which probably explains their widespread use in antioxidant screening. In turn, spectrometric techniques rely on the reaction of a radical, radical cation or complex with an antioxidant molecule capable of HAT and/or SET.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this biosensor was not used in the analysis of food samples. On the other hand, their collaborators developed a flow system for the antioxidant capacity estimation consisting of a bioreactor with immobilized XOD (for the generation of O 2 -radicals) coupled with a H 2 O 2 amperometric biosensor [56]. The bioreactor was constructed using Teflon® tubing containing XOD immobilized on cyanogen bromideactivated Sepharose 4B gel, silica gel or controlled-pore glass.…”
Section: Recent Strategies In the Development Of Biosensors Involvingmentioning
confidence: 99%